2015
DOI: 10.5433/1679-0359.2015v36n3supl1p2031
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Haemonchus, Cooperia, Trichostrongylus, and Oesophagostomum to ivermectin in dairy cattle in Paraná

Abstract: The objective of this study was to analyze the effect of ivermectin (3.15%) on gastrointestinal nematodes found in calves through the fecal egg count reduction test (FECRT), and larval culture in 16 animals from a school farm at the Universidade Estadual do Norte do Paraná. The animals were divided into two experimental groups: animals treated with ivermectin 3.15% (G1 group) and control animals (G2 group). Stool samples were collected from the animals twice i.e., on days 0 and 10 for fecal examinations. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
3
0
3
Order By: Relevance
“…Epidemiological studies of parasitic diseases in the North Pioneer mesoregion are scarce. However, the few studies on ruminants in this region have shown high parasite loads, which may reflect poor sanitary conditions and inadequate handling of these animals (HOLSBACK et al, 2013(HOLSBACK et al, , 2015(HOLSBACK et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies of parasitic diseases in the North Pioneer mesoregion are scarce. However, the few studies on ruminants in this region have shown high parasite loads, which may reflect poor sanitary conditions and inadequate handling of these animals (HOLSBACK et al, 2013(HOLSBACK et al, , 2015(HOLSBACK et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Quando adultos, medem até 3 cm e são identificados rapidamente devido sua especificidade de local. As espécies que afetam os bovinos são: Haemonchus placei e Haemonchus similis (Holsback, 2015).…”
Section: Haemonchus Sppunclassified
“…São encontrados mundialmente, principalmente nos subtrópicos e causam gastrite parasitária. As Research, Society and Development, v. 9, n. 11, e4089119908, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i11.9908 8 espécies que afetam os bovinos são Trichostrogylus axei e Trichostrogylus colubriformis (Urquhart et al, 1996;Holsback, 2015).…”
Section: Trichostrongylus Sppunclassified
“…The use of these endectocides has become customary in the last few decades, and macrocyclic lactones, particularly ivermectin, are among the most widely sold drugs for the control of cattle parasites (Delgado et al, 2009;Neves et al, 2014). However, the continuous use of ivermectin has resulted in anthelmintic resistance, a widespread problem reported in the states of Minas Gerais (Rangel et al, 2005), Rio de Janeiro (Cardoso et al, 2008), Santa Catarina (Souza et al, 2008), Mato Grosso do Sul (Borges et al, 2013), São Paulo (Neves et al, 2014), Paraná (Holsback et al, 2015) and Rio Grande do Sul (Ramos et al, 2016).…”
Section: Introductionmentioning
confidence: 99%